The Effect of Product Perception and Price Perception on Reference Book Purchase Decisions - Kuswanto Kuswanto; Refnida Refnida; Lulu Ratnadillah (Faculty of Economics, State University of Jakarta., 2021)
The decision to purchase reference books is a form of a student's positive attitude in meeting learning needs. This study was conducted to analyze the effect of product and price perceptions on reference book purchasing decisions. This research was conducted on 80 students of the Jambi University Economic Education Study Program class of 2017. Data were obtained from the results of a survey using a questionnaire. The data were analyzed using the logit regression model because the dependent variable data were categorical (buying and not buying). The results of the analysis show that product perception has a significant influence on purchasing decisions for reference books at an error rate (alpha) of 5 percent. Student perceptions of price also significantly influence the decision to purchase reference books at an error level (alpha) of 5 percent. Taken together, product perception and price significantly influence the purchasing decision of reference books. Thus, it is recommended for students to make the right decision by understanding the quality and usefulness of reference books to meet their learning needs and supported by adequate purchasing power.